Economic Value Added of the BREEAM Certification in the European Union Hotel Sector - Pechoultre de Lamartinie, Tanguy Thierry-Marie; Tyll, Ladislav; Balogh, Ivan; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This thesis aims to investigate what is the Economic Value Added (EVA) of the BREEAM Certification in the European Union Hotel Sector. 6 components (departmental revenues, utilities expense, maintenance expenses, management fees, discount rates and interest rates), linked to the EVA equation and specific to the hotel sector, were explored. Using a hotel guest questionnaire and interviews with hotel guests, lenders, operators, investors and valuers, the researcher aimed to understand whether obtaining the BREEAM certificate would lead to a fluctuation of these 6 components. The researcher concludes that the largest impact of the BREEAM certification on the European hotel sector can be observed on the utilities expense. Marginal and conditional impacts are also observed for discount rates, interest rates and departmental revenues. Finally, there was no significant impact observed on the management fees and the maintenance expenses.
Vedoucí práce: Ladislav Tyll
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses